AN ANALYSIS OF TURN TAKING IN MATA NAJWA PODCAST “SUSAHNYA JADI PEREMPUAN” - Monalisa Monalisa; Nofrika Sari; Yuhendra Yuhendra; Afdaleni Afdaleni; Haris Syukri; Albert Albert (LLDIKTI Wilayah X, 2024)
This research discusses the analysis of turn taking actions used in the Mata Najwa podcast episode “Susahnya Jadi Perempuan”. The aim of this research was to find the types of turn taking used in the Mata Najwa podcast and how the participants build a conversation. This research was conducted using qualitative methods. In collecting data the researcher utilized the observation method or Simak Libat Bebas Cakap (SLBC) from Sudaryanto (1998). In analyzing turn taking, the research applied the theory of George Yule (1995) and Stenstroom (1994). From the analysis of research finding, it was found that the strategy that appeared most often was Backchannels (15 data), Taking Over (12 data), Prompting (10 data), Interrupting (8 data), Overlaps (8 data), Filled Pause (8 data), Silent Pause (5 data), Appealers (4 data), Pause (5 data), Repitition (4 data), Giving Up (3 data), and Staring Up (1 datum).